Effects of probiotic on responses to stress: systemic modulation of microbiota-gut-brain axis - Liu, Yunpeng (My University, 2021)
Bacteria, especially symbiotic species in the gastrointestinal tract, have lived with human for long time and are involved in many aspects of host physiology. There is growing evidence that microbiota-gut-brain axis plays an important role in modulating the response to stress in both human and animals. Alterations in the gut microbiota can change the central nervous system function through effects on the endocrine, immune and nervous systems. Recent studies suggest that probiotic treatment may help to maintain resistance against the detrimental effects of stress though the microbiota-gut-brain axis. However, how potentially beneficial bacteria interact with specific immune and neural components, to mediate beneficial effects on behavior remain unclear. Using chronic social defeat stress, a model often used in post-traumatic stress disorder research, we found that administration of Lactobacillus rhamnosus JB-1 beginning 48 hours following chronic social defeat led to persistence of fear memory and social deficits. These effects were associated with changes in gene expression related to emotion and memory in the hippocampus. This was in contrast to previous studies showing that probiotic intervention during social defeat prevents stress induced deficits in social behavior. This indicates that timing of L. rhamnosus treatment in relation to stress exposure has important implications for effects of the bacteria on behavior. In relation to the mechanism of action of L. rhamnosus on behavior, we demonstrate through depletion and adoptive transfer experiments that CD4+CD25+ T cells in mice treated with JB-1 were necessary and sufficient for JB-1 induced anxiolytic and antidepressant-like effects. Evidence also suggested that Ly6Chi monocytes may be a downstream target inhibited by Tregs involved in the behavioral effects of the bacteria. We observed that JB-1 could also reduce the number of activated microglia in the hippocampus, and attenuate hypothalamic-pituitary-adrenal axis reactivity with the integrity of vagus nerve. Crucially we demonstrated that JB-1 induced promotion of peripheral Tregs, reduction in microglia activation in the hippocampus, and attenuation of HPA axis reactivity, were all inhibited following vagotomy indicating that vagus nerve integrity is required to maintain immune and endocrine linkages from gut microbes to the brain. These studies demonstrate prerequisites for beneficial probiotic effects on stress related behaviours including a specific time window in relation to stress exposure, the activation of regulatory immune cells, and undisrupted vagal nerve signalling. These findings highlight the inter-systemic communication of the microbiota-gut-brain axis in the stress response, and might help to unveil more therapeutic opportunities in relation to stress-related mood disorders.
Keywords: stress; microbiota-gut-brain axis; probiotics; immune regulation